Being as Relation in Luce Irigaray - Jones, Emma R. author. aut Link
XI, 166 p.
Keywords: Many scholars have struggled with Irigaray’s focus on sexuate difference, in particular with her claim that it is “ontological,” wondering if this implies a problematically naïve or essentialist account of sexuate difference. As a result, the ethical vision which Irigaray elaborates has not been taken up in a robust way in the fields of philosophy, feminism, or psychoanalysis. By tracing the notion of relation throughout Irigaray’s work, this book identifies a rigorous philosophical continuity between the three self-identified “phases” in Irigaray’s thought (despite some critics’ concerns that there is a discontinuity between these phases) and clarifies the relational ontology that underlies Irigaray’s conceptualization of sexuate difference – one that always already implies an ethical project. The text demonstrates that an understanding of Irigaray’s Heideggerian inheritance – especially prominent in her later texts – is essential to grasping the sense of the idea that sexuate difference is ontological – it concerns Being, rather than beings. This book further develops potential applications of this ontological notion of a “relational limit” for the fields of philosophy, feminism, and psychotherapy.